2009
DOI: 10.1590/s1516-35982009001200027
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho, características de carcaça e qualidade da carne de bovinos superprecoces das raças Canchim, Nelore e seus mestiços

Abstract: RESUMO -Oitenta e seis machos jovens, não-castrados, divididos em quatro grupos raciais -Nelore (n=20), Canchim (n=17), ½ Canchim × Nelore (CN) (n=25) e ¾ Canchim × Nelore (TQ) (n=24) -foram pesados a cada 28 dias para avaliação de ganho de peso (kg/dia), ingestão de matéria seca (kg/dia) e conversão alimentar. Ao atingirem peso de abate médio de 450 kg e espessura de gordura subcutânea superior a 4 mm, os animais foram abatidos para avaliação do peso e do rendimento de carcaça e de cortes comerciais do trasei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
13
1
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 20 publications
7
13
1
9
Order By: Relevance
“…Therefore, carcass must provide maximum amount of muscle, minimum of bone, and an amount of fat that varies depending on consumer preference. The proximate composition of the beef was similar between treatments and with values similar to those obtained by Lawler et al (2004), Freitas et al (2008), Razook et al (2002), Rubiano et al (2009), Souza et al (2009), and Sestari et al (2012, when working with Nelore cattle. The exception is ether extract content, which was lower, possibly due to the lower energy density of the diets used in this study compared with the aforementioned authors, who aimed at higher weight gain.…”
Section: Discussionsupporting
confidence: 78%
“…Therefore, carcass must provide maximum amount of muscle, minimum of bone, and an amount of fat that varies depending on consumer preference. The proximate composition of the beef was similar between treatments and with values similar to those obtained by Lawler et al (2004), Freitas et al (2008), Razook et al (2002), Rubiano et al (2009), Souza et al (2009), and Sestari et al (2012, when working with Nelore cattle. The exception is ether extract content, which was lower, possibly due to the lower energy density of the diets used in this study compared with the aforementioned authors, who aimed at higher weight gain.…”
Section: Discussionsupporting
confidence: 78%
“…Previous work shows that WBSF values tend to decrease with the addition of Bos taurus genes through crossbreeding (LAGE et al, 2012). The WBSF values also decrease as beef ageing time increases (BIANCHINI et al, 2007) and when animals are slaughtered at younger ages (BIANCHINI et al, 2007: RUBIANO et al, 2009.…”
Section: Resultsmentioning
confidence: 94%
“…However, another study examining Canchim cattle raised in a feedlot system showed higher phenotypic mean values for REA (91.30 cm 2 ) and BFT (5.00 mm), suggesting that the Canchim breed also responds well a feedlot system (Rubiano et al, 2009).…”
Section: Discussionmentioning
confidence: 94%